Assessment of neuromuscular electrical stimulation in critically ill patients: physical therapists' knowledge and barriers to its use - Janaina Almeida Fernandes; Marianne Lucena da Silva; Ana Cristina Trancho; José Roberto de Deus Macedo; Henrique Resende Martins; Paulo Eugênio Silva (Universidade de São Paulo, 2022)
ABSTRACT Transcutaneous neuromuscular electrical stimulation (NMES) is considered an important tool to prevent muscle mass and strength loss in patients admitted to intensive care units (ICU). This study aimed to evaluate physical therapists' profile and knowledge of NMES and identify the main barriers to its use in ICUs. This observational cross-sectional study was conducted via a structured questionnaire created by the authors. It consisted of 12 objective questions to analyze physical therapists' knowledge of NMES use in critically ill patients. Physical therapists were invited to participate in this study during an international symposium on NMES. In total, 56 physical therapists, with a mean age of 33.5±7.2 years and working an average of 9.7±7 years after graduation, completed the survey. Overall, 34 respondents worked in ICUs, of which only four (12%) reported regular NMES use in their ICUs. We found a low average of correct answers to our questionnaire (25%; 3/12). The main barriers reported to using NMES in ICUs were lack of knowledge (28; 50%) and equipment (24; 43%). The number of correct answers expert and non-expert physical therapists was not statistically significant (p=0.68). Thus, we observed participants' poor knowledge of NMES use in critically ill patients. Respondents showed that NMES has been underused in their ICUs. Lack of knowledge and equipment seems to be the main barriers for the use of NMES in ICUs.